Environmental enrichment using low walls and perches improves broiler welfare, without compromising productivity (Scientia Agropecuaria, 2025)
The study evaluated the impact of different environmental enrichment strategies on the performance and welfare of commercially raised broilers. The research, conducted in Paraná, Brazil, involved 690 birds allocated to three types of environments: control, with a low wall, and with a perch. The performance of the birds was monitored through indicators such as feed conversion, live weight (plucked and eviscerated), and cut yields (wing, thigh, drumstick, breast, and back weight). There were no significant differences in feed conversion and yields between the environments, except for wing weight, which was higher in environments with a perch for males. Females raised in an environment with a low wall showed higher live and eviscerated weight, while thigh weight was lower in environments with a perch. Welfare variables, such as Latency to Lie and Fluctuating Asymmetry, showed no significant differences between the environments. However, females in the control and low wall environments had a higher incidence of calluses on their feet compared to those in the perch environment. Joint injuries (Hock Health) did not show significant differences between the types of enrichment. These results suggest that, although environmental enrichment may benefit some aspects of welfare, its impact on broiler performance and joint health needs to be better understood, particularly in relation to the long-term effects of different enrichment types on locomotor health, muscle development, and the prevention of joint injuries. Future studies should focus on the physiological mechanisms behind these effects, including the role of enrichment in reducing stress and promoting more natural behaviors that may influence bone density and joint function.
Keywords: Animal welfare; joint injuries; locomotor problems; zootechnical performance